Nutritional Awareness of Extra Virgin Olive Oil: Empirical Evidence from Consumer Perceptions and Health Beliefs - Manuela Oliverio; Luigi Gencarelli; Martina Michienzi; Sonia Bonacci; Antonio Aquino; Antonio Procopio (Foods, 2026)
Extra virgin olive oil (EVOO) is a key component of the Mediterranean diet and a functional food whose health properties are mainly attributed to phenolic compounds. Despite the availability of EFSA-approved health claims, consumers often rely on heuristic cues that may not correspond to scientifically recognized quality indicators. A cross-sectional online survey involving 516 Italian consumers was conducted to investigate consumption patterns, health-related beliefs, territorial identity, and sensory quality perception. Descriptive analyses, regional comparisons, and a multivariable logistic regression model predicting sensory misperception were performed. Most respondents reported frequent EVOO consumption and willingness to pay a premium for certified products. Territorial identity, trust in local producers, and origin-related cues emerged as important dimensions of quality perception. Although respondents generally recognized the health relevance of antioxidants and unsaturated fatty acids, misconceptions regarding sensory indicators were common. Specifically, 41% of respondents associated sweetness with EVOO quality, whereas bitterness and pungency were less frequently recognized. Greater perceived knowledge of EVOO health properties was associated with a lower likelihood of identifying sweetness as an indicator of EVOO quality. Overall, consumer evaluation of EVOO reflected the interaction of informational, symbolic, and experiential dimensions, highlighting the potential relevance of communication strategies and sensory education initiatives whose effectiveness should be evaluated in future research.